Noun Phrases or Syntagmatic Compounds? A Discussion on the Spanish Variety Used in Valle de Aburrá - Orduña López, José Luis (Íkala, Revista de Lenguaje y Cultura, 2019)
This article aims primarily at reflecting, from a theoretical viewpoint, upon the criteria underlying the distinction between a syntagmatic compound and a noun phrase, in order to get to the more objective stance as possible regarding this issue, without assuming such a distinction even exists. The theoretical framework brings definitions of the concepts dealt with, on the basis of an exclusivity criterion —idiomaticity. This theoretical section is applied to the analysis of phraseological units that make up the corpus of this work, which were taken from the lexicographical corpus in the research project A Descriptive Dictionary of Valle de Aburrá Spanish, which has been developed by Universidad de Antioquia’s Faculty of Communications from 2005 (with the involvement of Universidad de Medellín from 2007 on). Another section is devoted to the treatment that the units under study might receive in a monolingual dictionary, both in their macro-structure or micro-structure. Finally, an appendix with phraseological units and their meaning is included.